Effectiveness of Soil Solarization for the Control of Soft Rot Disease in Ginger - Vilasini T N (Department of Plant Pathology, College of Horticulture, 1996)
The effectiveness of soil solarisation for the control of soft rot disease in ginger was studied at the College of Horticulture, Vellanikkara, Thrissur during March 1992 to December 1993. The beds were inoculated with Pythium aphanidermatum, five days before the solarisation. Transparent, 150 guage polyethylene sheets were used for solarizing the beds. Maximum soil temperatures recorded were 63.00, 59.00 and 46.50 at 5, 10 and 15 cm depths in solarized soil, while, that in non-solarized soils were 49.50, 43.00 and 40.00C, respectively, at 5,10 and 15 cm depths. Temperature in the solarized soil at 5 cm depth was above 50.00 C for the entire solarisation period and above 55.00 C for 38 days, while, at 10 cm depth the temperature was above 50.00 C for 35 days and above 55.00 for five days. The soil temperature at 15 cm depth never reached 50.00 C during the solarisation period. Based on the soil and air temperature recorded, two simple regression equations at 5 and 10 cm depths, one simple equation at 15 cm depth and one multiple regression equation at 10 cm depth were developed for predicting soil temperature under polyethylene mulch. Rate of germination in ginger was enhanced by solarisation. Significant effect of solarisation was observed in controlling the pre and post-emergence rotting in ginger. Increasing the period of solarisation from 30 to 45 days did not result in a corresponding reduction in the pre-emergence rotting. Trichoderma incorporated neem cake amended 30 day solarized treatment was highly effective and recorded cent percent control of the soft rot disease, while, maximum disease incidence (90.67%) was in Trichoderma incorporated neem leaves amended 45 days solarized plots. Reduction in Pythium population ranging from 79.49 to 99.1 per cent was observed in solarized plots immediately after the removal of polyethylene sheets. Solarization reduced the total fungal, bacterial, actinomycetal and Pseudomonas sp. population in the field. Plants grown in solarized plots showed better colonization of VAM and Azospirillum. Significant reduction in the nematode population was recorded by solarisation. Solarization had a profound suppressive effect on the weed population and it lasted till harvest. Solarization effect was more pronounced in dicots. Eventhough, solarisation substantially reduced weed population, its effect was less in the edges. Bulbostylis barbata, Cynodon dactylon and Cyperus rotundus survived the solarisation effect. Increased growth response of ginger plants was observed as a result of solarization. Growth parameters like height, number of leaves/plant, number of tillers, number of roots, leaf length, leaf breadth, fresh weight of shoots and rhizomes were influenced by solarisation. Significant increase in the yield was obtained through solarisation. Trichoderma incorporated and neem cake amended 30 days solarized treatment gave the maximum yield/plant (623.23 g) and also per plot yield (10159.57 g), which was 5361 per cent more than that of control. Availability of nitrogen, phosphorus and potassium was improved by solarisation. The initial cost of solarization is comparatively high, an amount of Rs. 52,500/- is required for solarizing one hectare of ginger field. An additional profit generated from this technique was Rs. 40,136/ha for 30 days solarisation.